Feasibility of Terahertz Time-Domain Spectroscopy to Detect Carbendazim Mixtures Wrapped in Paper - Binyi Qin; Zhi Li; Zhihui Luo; Huo Zhang; Yun Li (Journal of Spectroscopy)
The purpose of this work was to detect carbendazim mixtures wrapped in paper. Unlike previous reports of THz-TDS for detecting pesticide residue, this work focused on detecting pesticide residue in packaged foods. Different weight ratios of carbendazim in polyethylene and in rice powder were detected qualitatively and quantitatively. Results show that pure carbendazim, polyethylene, and rice powder can be easily distinguished from each other. However, when the weight ratio was low, the absorbance of the mixture was similar with that of pure polyethylene and rice powder. With the help of SVM, carbendazim could be qualitatively detected in low weight ratio mixture successfully. Moreover, PLS and SVR were selected to quantitatively detect carbendazim mixtures. SVR has higher R and lower RMSECV, RMSEC, and RMSEP than PLS model. Lasty, the results also indicate that THz-TDS is a potential tool to detect pesticide residue in packaged foods qualitatively and quantitatively.